2009
DOI: 10.1063/1.3036955
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional silicon photonic crystals fabricated by two photon phase mask lithography

Abstract: We describe the fabrication of silicon three dimensional photonic crystals using polymer templates defined by a single step, two-photon exposure through a layer of photopolymer with relief molded on its surface. The resulting crystals exhibit high structural quality over large areas, displaying geometries consistent with calculation. Spectroscopic measurements of transmission and reflection through the silicon and polymer structures reveal excellent optical properties, approaching properties predicted by simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…This capability is particularly useful for photonic crystals [100][101][102] and broadband circular polarizers. [ 28 , 103 ] TAP occurs due to two-photon absorption (TPA) where an electronic transition occurs in a molecule that absorbs energy from two photons simultaneously.…”
Section: Multi-photon Lithographymentioning
confidence: 99%
“…This capability is particularly useful for photonic crystals [100][101][102] and broadband circular polarizers. [ 28 , 103 ] TAP occurs due to two-photon absorption (TPA) where an electronic transition occurs in a molecule that absorbs energy from two photons simultaneously.…”
Section: Multi-photon Lithographymentioning
confidence: 99%
“…Two-photon lithography has been used to develop masks with conformable elements [99] and molded reliefs that allow for nanopatterning by close contact exposures using near fields [107,108]. These masks were recently used to fabricate Si/air photonic crystals over large areas with high fidelity to the design geometries consistent thus displaying properties that agreed well with theoretical results [102].…”
Section: Nanoscaled Featuresmentioning
confidence: 58%
“…We begin our discussion with 3D photonic crystals [100,101] which have garnered much attention in recent years due to their potential application to develop thresholdless semiconductor lasers, singlemode light-emitting diodes, ultra-compact low loss waveguides for high speed information processing, etc. [102,103] The biggest challenge in the development of these devices is the precise fabrication required to build them which demands precise structural control in three dimensions [104][105][106]. Two-photon lithography has been used to develop masks with conformable elements [99] and molded reliefs that allow for nanopatterning by close contact exposures using near fields [107,108].…”
Section: Nanoscaled Featuresmentioning
confidence: 99%
“…The refl ectance response (Figure 2 c) shows broad refl ectivity peaks approximately 170-180 nm wide for all the three devices with the bandedge at the short wavelength appearing at 710 nm for a = 300 nm, 640 nm for a = 250 nm, and 615 nm for the a = 220 nm but it has already been demonstrated that its repetitive nature allows for easy automation for large scale production using step-and-repeat lithography employed in CMOS fabrication. [ 19 ] Alternative approaches involving a single step multilayer 3D template fabrication based on direct laser write, [ 23 ] holography [ 24 ] and phase mask lithography [ 25 ] can also potentially reduce fabrication time and cost. Figure 1 b shows a scanning electron microscope (SEM) image of the top and crosssectional view of a 300 nm lattice constant PC.…”
Section: Doi: 101002/adma201001965mentioning
confidence: 99%